Representasi Nilai-Nilai Ajaran Masyarakat Samin dalam Film Lari dari Blora - Indra Bagus Kurniawan; Turnomo Rahardjo (Interaksi Online, 2021)
The Samin community is known as an conservative community group, unwilling to attend formal schools, unwilling to submit to government regulations, unwilling to accept outside culture, and a lot of closure to outsiders. The film Lari dari Blora seeks to fight this stigma by presenting the teachings of the Samin community which are used as guidelines for everyday life in the village environment of Samin. This film tells the story of various problems that occur in cultural life, where they must defend their identity even in unfavorable situations. This study aims to explain how the life of the Samin people in Blora Regency which is shown in the film Lari dari Blora and to explain how the representation of the teachings of the Samin people is shown in the film Lari dari Blora using qualitative research methods. This research refers to the constructivism paradigm. The theory used in this research is Roland Barthes' semiological theory. Data collection techniques used in this study are documentation and observation. The results of this study reveal that the film Lari dari Blora wants to give a message that the Samin people in Blora Regency live in a sphere of simplicity and harmony in the midst of technological developments and globalization currents that make the Samin people struggle to maintain the culture that has been adopted and passed down by their ancestors they. The film Lari dari Blora gives a message that the Samin community will no longer close themselves to the presence of outsiders who enter their group, and begin to open themselves up to socialize with groups that have different principles and teachings.